2003
DOI: 10.1080/0267829031000121233
|View full text |Cite
|
Sign up to set email alerts
|

Free-standing films of twist grain boundary TGBAand UTGBC*liquid crystals studied by fluorescence confocal polarizing microscopy

Abstract: The director structures, meniscus profile, and defects in free-standing films of the twist grain boundary TGB A and UTGB C* liquid crystals were studied. The films were characterized by a combination of polarizing microscopy and fluorescence confocal polarizing microscopy. Five principal regions of meniscus were distinguished. When film thickness in the meniscus is much smaller then the TGB pitch, there is no difference between the free-standing films of TGB and ordinary smectic A liquid crystals. When the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…To end this section, let us mention that very similar striped patterns, with a varying periodicity, were also reported in the meniscus of twist grain boundary (TGB) LCs featuring SmA and SmC* blocks. 13 3.1.2 Focal conic domains. As we go further away from the film, the stripes give way to a two-dimensional (2D) ordered array of focal conic domains (FCDs).…”
Section: Textures In the Outer Meniscusmentioning
confidence: 99%
See 2 more Smart Citations
“…To end this section, let us mention that very similar striped patterns, with a varying periodicity, were also reported in the meniscus of twist grain boundary (TGB) LCs featuring SmA and SmC* blocks. 13 3.1.2 Focal conic domains. As we go further away from the film, the stripes give way to a two-dimensional (2D) ordered array of focal conic domains (FCDs).…”
Section: Textures In the Outer Meniscusmentioning
confidence: 99%
“…Seemingly similar splay domains, together with additional features, were also noticed by Maclennan in the meniscus of smectic ferroelectric compounds. 11 Dhara et al 12 and Smalyukh et al 13 further explored the behavior of FSFs made of twist grain boundary TGB A and undulating twist grain boundary UTGB C* compounds. Optical microscopy observations reveal that the meniscus of these LCs also exhibits radial stripes with a varying periodicity that depends on the meniscus thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8-10, 12, 32] Samples, without or with only few of these birefringent stripes show even an inverted electrooptic switching characteristic. First, conventional polarizing optical microscopy (POM) and fluorescence confocal polarizing microscopy (FCPM) [33][34][35][36] were applied to clarify the origin and director field topology of the birefringent stripes observed in these homeotropic samples. The latter method allows three-dimensional imaging of the local director orientation by measuring the fluorescence intensity of a dichroic dye dissolved in the liquid crystal.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that only light emitted from the focal region of the confocal beam is collected, a pinhole is used at the focal point of the light emitted from the voxel of interest to allow a spatial resolution of better then 1 µm in all three dimensions. This technique has previously been used to examine such structures as twist-grain boundaries in free-standing liquid crystal films [16], defects in biaxial smectic-A materials [17] and focal-conic domains in self-assembled structures [18]. It has also been shown that FCPM can be used to probe the cholesteric structure (of pitch p) in a Grandjean-Cano wedge cell [19] provided that the parameter p∆n / 2λ is small enough to limit the influence of the Maugin effect on the resulting images.…”
Section: Fluorescence Confocal Polarizing Microscopy (Fcpm)mentioning
confidence: 99%